2017
DOI: 10.20849/aes.v2i3.192
|View full text |Cite
|
Sign up to set email alerts
|

Adopting Digital Technology in Teaching and Learning Environment in Early Childhood Education Classes in Nairobi County, Kenya

Abstract: Dispositions towards use of digital technologies in modern early childhood settings have dramatically transformed aspects in education sector through development and integration of technology into education policy, curriculum and practice. Digital technology as a tool in instruction benefits learner's fine motor skills, language and communication readiness, mathematical thinking as well as positive attitudes towards learning. Conversely inadequate educational and digital competence hampers teachers in Early Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…In East Africa, studies revealed a low usage rate of ICT tools including tablets, in education. In Uganda study by Tulinayo et al (2018) indicates a negative attitude and a lack of a systematic teaching approach, while research in Kenya by Amolloh et al (2017) revealed positive perceptions of classroom technology use. These differences underscore the need for investigations into awareness of pedagogical understanding to enhance tablet utilization for educational purposes.…”
Section: Introductionmentioning
confidence: 99%
“…In East Africa, studies revealed a low usage rate of ICT tools including tablets, in education. In Uganda study by Tulinayo et al (2018) indicates a negative attitude and a lack of a systematic teaching approach, while research in Kenya by Amolloh et al (2017) revealed positive perceptions of classroom technology use. These differences underscore the need for investigations into awareness of pedagogical understanding to enhance tablet utilization for educational purposes.…”
Section: Introductionmentioning
confidence: 99%